2000
DOI: 10.1038/sj.ejhg.5200476
|View full text |Cite
|
Sign up to set email alerts
|

Giant axonal neuropathy locus refinement to a < 590 kb critical interval

Abstract: Giant axonal neuropathy (GAN) is a rare autosomal recessive neurodegenerative disorder, characterisedclinically by the development of chronic distal polyneuropathy during childhood, mental retardation, kinky or curly hair, skeletal abnormalities and, ultrastructurally, by axons in the central and peripheral nervous systems distended by masses of tightly woven neurofilaments. We recently localised the GAN locus in 16q24.1 to a 5-cM interval between the D16S507 and D16S511 markers by homozygosity mapping in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
(25 reference statements)
2
20
0
Order By: Relevance
“…Linkage of families 9, 14, and 15 to the GAN locus was previously demonstrated by homozygosity mapping Cavalier et al, 2000). Genetic studies of family 16 with polymorphic markers LC8, LC6, D16S3098, GAAT2CO8 and D16S505 demonstrated linkage to 16p24.1 with a LOD score of 3.1 at θ = 0 (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Linkage of families 9, 14, and 15 to the GAN locus was previously demonstrated by homozygosity mapping Cavalier et al, 2000). Genetic studies of family 16 with polymorphic markers LC8, LC6, D16S3098, GAAT2CO8 and D16S505 demonstrated linkage to 16p24.1 with a LOD score of 3.1 at θ = 0 (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The three families affected by GAN were genotyped with polymorphic markers present in the GAN region on chromosome 16q24.1 (LC8, LC6, LC5, D16S3098, LC1, LC3, LC2, and D16S505). 13 Forward primers were labelled with 6-Fam, Hex, or Ned fluorochromes (Applied Biosystems Inc, Foster City, California, USA). Polymerase chain reactions (PCRs) were performed in a final volume of 10 ml containing 20 ng of genomic DNA, 1mM dNTP, 16 NBL buffer, 0.50mM of each primer, and 0.1 IU of Taq polymerase.…”
Section: Microsatellite Marker Analysismentioning
confidence: 99%
“…An aggregation of cytoplasmic intermediate filaments was also seen in other cell types, including fibroblasts, endothelial cells, melanocytes, and Langerhans cells, indicating a generalised disorganisation of cytoplasmic intermediate filaments in GAN. 9 10 We and others have located the GAN disease locus to 16q24.1 by homozygosity mapping in consanguineous families, [11][12][13] and we have recently identified the defective gene by positional cloning. 14 We found one single nucleotide insertion, nine missense, and four nonsense mutations, distributed throughout the 11 exons of the GAN gene, in 12 families of various origins.…”
mentioning
confidence: 99%
“…GAN is a recessive disease (4,5,16,17) caused by mutations in the GAN gene (encoding for gigaxonin), which is located on chromosome 16q24. Over 30 distinct mutations distributed throughout the GAN gene have been identified (9,11,16).…”
Section: Introductionmentioning
confidence: 99%